Effect of Nigella Sativa (Kalozira) Oil on Pain in Long Evans Rats - Jerin, Ismoth Ara; Begum, Noorzahan (Journal of Bangladesh Society of Physiologist, 2018)
Background: For thousands of years, Nigella sativa has been used in many countries as a spice as well as a protective and curative remedy for numerous health disorders. Nigella sativa oil (NSO) suppressed pain in animal models. Objective: To assess the effects of Nigella sativa oil on pain after single administration with three increasing doses in rat models. Methods: This experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2016 to February 2017. For this, 20 (twenty) Long Evans rats (200±20) of both sexes were divided into control ( 10 ml/kg of 1% solution of Tween 20) and experimental groups (NSO 0.5, with 0.5 ml/ kg NSO; NSO 1, with 1 ml/kg NSO; NSO 1.5, with 1.5 ml/kg NSO) with 5 rats in each group.. To assess nociceptive pain, central analgesic system and inflammatory pain ,early phase (1st-5th minutes); inter phase (6th-15th minutes) and on late phase (16th-60th minutes) of formalin test respectively were observed. All the agents were given intraperitoneally in a single dose just one hour before the formalin test. In all phases, total frequency of jerking and total duration of flexing and licking of right hind paw were counted after administration of subcutaneous formalin (50 µL, 2.5%) injection. Statistical analysis was done by ANOVA, followed by Bonferroni’s post hoc test. Results: In early phase, NSO significantly reduced the jerking (p ≤0.001, in all doses) and flexing and licking (p≤0.001, in higher 2 doses). In interphase, jerking was significantly (p ≤ 0.01) lowered after 1.5 ml/kg of NSO but flexing and licking were significantly lowered by at all 3 doses (p ≤0.05, p ≤0.001, p ≤0.001,). In addition, in late phase jerking and flexing and licking were reduced by higher 2 doses (p ≤0.001, ) and all 3 doses respectively (p ≤0.001, in all doses). Conclusion: From this study, it may be concluded that, NSO possess analgesic effect and higher two doses were more effective than lower doses. J Bangladesh Soc Physiol. 2018, June; 13(1): 1-7